2015
DOI: 10.1186/s12967-015-0472-6
|View full text |Cite
|
Sign up to set email alerts
|

Perspective of synaptic protection after post-infarction treatment with statins

Abstract: Stroke is the second most common cause of death in people over 45 years of age in Colombia and is the leading cause of permanent disability worldwide. Cerebral ischemia is a stroke characterized by decreased blood flow due to the occlusion of one or more cerebral arteries, which can cause memory problems and hemiplegia or paralysis, among other impairments. The literature contains hundreds of therapies (invasive and noninvasive) that exhibit a neuroprotective effect when evaluated in animal models. However, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Statins inhibit the synthesis of valid isoprenoids, such as farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP), which are important intermediates for the post-translational modification of Rho GTPases, leading to the modulation of various cellular functions, e.g., decreased structural damage of the cytoskeleton [125]. Additionally, Gutierrez-Vargas et al proved that atorvastatin used after ischemic stroke influences the recovery of the actin cytoskeleton and stabilizes microtubules by increased activity of Rac and RhoA reduction [126]. Another mechanism of neuroprotection by statins involves their influence on inflammation through a number of proinflammatory cytokines.…”
Section: Influence Of Statins On Glutamatergic Transmission and Their Neuroprotective Effectmentioning
confidence: 99%
“…Statins inhibit the synthesis of valid isoprenoids, such as farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP), which are important intermediates for the post-translational modification of Rho GTPases, leading to the modulation of various cellular functions, e.g., decreased structural damage of the cytoskeleton [125]. Additionally, Gutierrez-Vargas et al proved that atorvastatin used after ischemic stroke influences the recovery of the actin cytoskeleton and stabilizes microtubules by increased activity of Rac and RhoA reduction [126]. Another mechanism of neuroprotection by statins involves their influence on inflammation through a number of proinflammatory cytokines.…”
Section: Influence Of Statins On Glutamatergic Transmission and Their Neuroprotective Effectmentioning
confidence: 99%
“…A possible explanation for these discrepancies could be based on the fact that stroke can be either ischemic or haemorrhagic, and there are evidences supporting an association between elevated cholesterol and increased risk of ischemic stroke, but also showing a relationship between low cholesterol levels and increased risk of haemorrhagic stroke [30]. So, while disagreements are still present on the usefulness of statins in the primary prevention of acute stroke, there is a wide consensus on the positive aspects of statins treatment in secondary prevention after stroke or transient ischemic attack for diminishing the menace of suffering a new stroke [65][66][67][68]. Even in haemorrhagic stroke, some data from recent studies suggest that statin therapy could improve the outcome after spontaneous intra-cerebral haemorrhage and statin therapy should be not discontinued [69][70][71].…”
Section: Strokementioning
confidence: 99%
“…Moreover, overactivation of the NMDA receptors due to excitotoxicity leads to alteration in synaptic proteins localization, probably due to cytoskeleton disassembly, translation shutdown, decreased endocytosis, and activation of calpains. The final consequence is synaptic disruption and neuronal loss [ 63 ].…”
Section: Loss Of Synapses In the Penumbra: From Synaptic Failure Tmentioning
confidence: 99%
“…It has been shown that statins (such as simvastatin or atorvastatin), which are drugs used against hypercholesterolemia, can have beneficial effects in stroke by not only decreasing inflammation, oxidative stress, and improving the endothelial function but also by restoring proteins related to neuronal connectivity [ 63 , 139 ]. Similarly, new migraine treatments influence SD by targeting ion channels or neuromodulation [ 140 ] or by trying to control neuronal polarization using electrical fields [ 141 ].…”
Section: Therapeutic Options To Salvage Neurons In the Penumbramentioning
confidence: 99%